2022
DOI: 10.3390/biology11101535
|View full text |Cite
|
Sign up to set email alerts
|

Cmcrf1, a Putative Zn2Cys6 Fungal Transcription Factor, Is Involved in Conidiation, Carotenoid Production, and Fruiting Body Development in Cordyceps militaris

Abstract: Cordyceps militaris is a high-value medicinal and edible fungus that produces many bioactive compounds, including carotenoid, and thus, improving the carotenoid productivity of C. militaris will increase its commercial value. However, little is known about the genetic regulatory mechanism of carotenoid biosynthesis in C. militaris. To further understanding the regulatory mechanism of carotenoid biosynthesis, we performed a large-scale screen of T-DNA insertional mutant library and identified a defective mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…As early as 2011, Zheng et al [58] constructed a C. militaris mutant library and identified the functions of these genes. He et al [59] obtained a defective mutant using ATMT with a colony phenotype that was white after light exposure; the results showed that the Cmcrf1 gene was involved in fruiting body development and carotenoid biosynthesis. In 2019, Lou Haiwei et al [55] transformed Cmtns into a deleted mutant (∆Cmtns) using ATMT, discovering that Cmtns significantly affects carotenoid biosynthesis; this provides an important basis for the future study and promotion of carotenoid production.…”
Section: Genetic Manipulation Of C Militarismentioning
confidence: 99%
“…As early as 2011, Zheng et al [58] constructed a C. militaris mutant library and identified the functions of these genes. He et al [59] obtained a defective mutant using ATMT with a colony phenotype that was white after light exposure; the results showed that the Cmcrf1 gene was involved in fruiting body development and carotenoid biosynthesis. In 2019, Lou Haiwei et al [55] transformed Cmtns into a deleted mutant (∆Cmtns) using ATMT, discovering that Cmtns significantly affects carotenoid biosynthesis; this provides an important basis for the future study and promotion of carotenoid production.…”
Section: Genetic Manipulation Of C Militarismentioning
confidence: 99%
“…The vegetative growth of a CmSnf1 deletion mutant (Δ CmSnf1 ) was reduced by 42.2% with arabinose as a sole carbon source in C. militaris , and CmSnf1 was necessary for mycelium to penetrate the insect cuticle to form the fruiting body on silkworm pupae, consistent with the down-regulation of chitinase- and protease-encoding genes in Δ CmSnf1 [ 8 ]. The Δ Cmcrf1 and Δ Cmfhp mutant cultured on rice medium did not produce fruiting bodies and did not have an impact on the mycelia growth of C. militaris [ 9 , 10 ]. In addition, light is an essential factor for pigment formation and fruiting body development in C. militaris [ 11 ].…”
Section: Introductionmentioning
confidence: 99%